How to improve the implementation of guidelines on cancer-related thrombosis. Issue 3 (March 2011) - Debourdeau, Philippe; Beckers, Marielle; Géérôôme, Patrick; Durant, Céécile; Lacoin, Quitterie; Debourdeau, Antoine; Bancel, Dominique Farge
Venous thromboembolism (VTE; defined by deep-vein thrombosis, central venous catheter-related thrombosis or pulmonary embolism) is a major therapeutic issue in cancer patients. VTE is reported in 15––20% of patients with cancer and is an independent prognostic factor and a leading cause of death. In this population, low-molecular-weight heparins have been shown to be superior to vitamin K antagonists. The Italian Association of Medical Oncology, the National Comprehensive Cancer Network, the American Society of Clinical Oncology, the French ''Institut National du Cancer'', the European Society of Medical Oncology and the American College of Chest Physicians have all published specific guidelines, but their implementation is still low in clinical practice. Methodological assessment of these guidelines was performed using the Appraisal of Guidelines Research & Evaluation Instrument. None of the guidelines on thrombosis and cancer have sought for patients'' preferences, nor were they tested among target users. VTE in cancer patients requires a multidisciplinary approach but downstream of the guidelines publication, the potential organisational barriers in applying the recommendations have not been discussed. Tolerance and cost––effectiveness of long-term use of low-molecular-weight heparin may account for the large heterogeneity seen in daily clinical practice. Homogenization of guidelines in international consensus working groups followed by educational and active implementation strategies would be very valuable in order to improve the care of VTE in cancer patients.